Phenomenographic approach to interculturality in basic education-speaking aimara teachers from Metropolitan Lima - Escobar-Maquera, Edi (2022)
This research shows the qualitatively different ways in which Aymara-speaking Basic Education teachers experience interculturality in an urban context of Metropolitan Lima, which concentrates the largest number of speakers of indigenous languages in Peru. The objective of the study is to analyze the perceptions of Aymara-speaking teachers about interculturality. This is a qualitative research based on phenomenography, where a semi-structured in-depth interview was applied to 10 participants intentionally selected for convenience under the saturation criterion. From the inductive analysis of the corpus, 6 categories emerged: interculturality as valuing our language, interculturality as speaking our language, interculturality as dialogue for coexistence, interculturality as inclusion of diversity, interculturality as dialogue of knowledge and interculturality as a practice of tolerance.